Modeling influences of container freight ocean shipping and road haulage costs to last-mile trade corridors on price inflation trend in west africa - Nwokedi; Theophilus Chinonyerem; Callistus Chukwudi Ibe; Mbachu Justice; Okafor Cajethan Onyedikachi (Journal of Management and Science, 2022)
The study investigated the influence of the TEU container freight ocean transportation cost from Shangai port, China to Lagos seaport in West African and the road haulage cost of TEU container freight from Lagos ports to the hinterland markets in Nigeria on the increasing trend of inflation in the prices of imported market commodities in the economy. It employed ex-post factor research design in which time series secondary data covering a nine (9) years period from 2010 to 2018 was obtained for the TEU container freight ocean transport cost, price inflation rates in the economy, TEU container freight road haulage cost from Lagos seaports to the regional hinterland markets in Kano in the north, Onitsha in the east, and Alaba international market in the west. The multiple regression analysis method was used to analyze the obtained data using the OLS method. The findings indicate that, cumulatively, the TEU container freight ocean transport cost and road haulage costs borne by shippers in transporting imports from China through the Lagos seaports to the regional hinterland markets in Nigeria, West Africa, does not significantly influence levels of inflation in commodity prices in the Nigerian economy. The study concluded that, though transport cost influences price inflation rates in the economy; it is not a significant or determinant factor of inflation in commodity prices in the Nigerian economy. Recommendations were proffered on the basis of the research findings.